Combination of arsenicum trioxide and all trans retinoic acid in the treatment of relapsed acute promyelocytic leukemia - A. N. Sokolov; E. N. Parovichnikova; V. V. Troitskaya; L. A. Kuzmina; V. G. Savchenko (Онкогематология)
From 2001 to 2013 eleven patients with relapsed acute promyelocytic leukemia (APL) (median age – 30 years) received arsenicum trioxide (ATO). ATO was administered as a 2nd line relapse therapy in 9 patients, as 1st line relapse therapy in 2 patients. ATO was administered in a dose of 0.1 mg/kg in 7 patients, 0.15 mg/kg – in 4 patients. The induction duration was 14 days in 3 patients, 24–35 days in 2 patients, 60 days in 6 patients. From the 1st day of ATO patients received 45 mg/m2 all trans retinoic acid (ATRA) (1 patient – from day 29 of ATO therapy). Maintenance therapy ATO + ATRA (10–14 days courses, every four weeks) patients were receiving during 10–15 months. 2 from 3 patients with molecular relapses achieved remission lasting 57 and 89 months after the 14-day ATO courses. 1 from 2 patients with bone marrow relapse achieved remission lasting 27 months after the 24–35-day ATO courses. 60-day courses were effective in 5 of 6 patients: in 4 of which remission are retained during 16, 19, 27, 57 months; 1 patient was relapsed after 12 months; 1 patient did not achieve molecular remission. 3 patients received allogeneic hematopoietic stem cell transplantation (alloHSCT), 2 of which alive in remission. 1 patient received autologous hematopoietic stem cell transplantation in the 2nd molecular remission (alive in remission). 4 patients died: 1 – in the 3rd relapse (duration of 2nd remission – 9 months), 1 – in remission from complications after alloHSCT, 1 – from APL progression, 1 – sudden death in 2nd remission lasting 72 months. ATO + ATRA for 60 days with supportive therapy are more effective than chemotherapy in the treatment of APL relapse. Interferon α + ATRA are inappropriate treatment of APL molecular and cytogenetic relapse. Using autologous HSCT in 2nd molecular remission will improve the results of APL relapse treatment.